Vicenin-2, a potential anti-inflammatory constituent of Urtica circularis - Marrassini, Carla (2011)
Vicenin-2, a flavonoid glycoside, was isolated and identified from an ethanol extract of the aerial parts of Urtica circularis. This crude extract was found to possess significant anti-inflammatory activity in a carrageenan-induced rat hind paw edema model (41.5% inhibition at a dose of 300 mg/kg; ip). The effects of 1 on several inflammatory mediators were investigated. In cultured murine macrophages, this compound modified LPS-induced total nitrite and TNF-R production, in addition to the LPS-induced translocation of the nuclear factor NF-kB.